Control interno administrativo del Colegio Fiscal Técnico Agropecuario “Balzar”, periodo 2011 - Meza Zambrano, Sayra Melissa (2013)
The present study was conducted in the province of Guayas, Balzar Canton, College Attorney technical agricultural "Balzar", located at 1.5 km of the via Balzar - Palenque, whose geographical situation is 30´00´´ 1 ° of South latitude and 80 ° 0´00´´ West longitude at an altitude of 42 m. The investigative phase lasted for 30 days. He had as objectives: establish a diagnosis of functions by areas through the flow of the "BALZAR" College agricultural technical Fiscal processes. Determine the level of trust and control in the "BALZAR" College agricultural technical Fiscal risk. Assess internal administrative control in the "BALZAR" College agricultural technical tax. Issue the report with their respective opinions, conclusions and recommendations and elaborate a proposal for manual control interno. Se applied the questionnaire of internal control staff who is related in the administrative process of the Administrative Department of the "Balzar" College agricultural technical tax in order to obtain accurate and reliable information on the topic to develop.There are deficiencies in the school tax technical agricultural "Balzar" process flow, since they do not comply with certain guidelines for best resultados En school tax technical agricultural "Balzar" most of their areas are at a low level of confidence and therefore the risk of control is high. College tax technical agricultural "Balzar" had not made any assessment to determine the level of administrative risk in the institution. In the "Balzar" College agricultural technical tax does not exist an administrative manual.